A Theory of Digital Ecosystems - Paul Heidhues; Mats Köster; Botond Kőszegi (CESifo GmbH, 2024)
We develop a theory of digital ecosystems built on the premise that a multi-market firm can steer users it has in one market toward its products in other markets. Due to this “cross-market leverage,” a leader in an “access-point” market (where users begin their online journeys) derives a high value from offering services in connected markets (where users continue their journeys), and can thus make profitable takeovers. Indeed, because the firm has the outside option of acquiring, and steering users toward, its target's competitor, it can take over the target at a discount. In contrast, other firms have no or smaller incentives for takeovers, explaining why ecosystems grow out of market leaders at access points. Conversely, cross-market leverage also implies that once an ecosystem has grown, it has an increased value of controlling access points, so it may go to great lengths to dominate these markets. Our theory suggests that ecosystems have mixed implications for consumer welfare. Under plausible assumptions, a to-be ecosystem takes over market leaders, and this consolidation of good services across markets benefits consumers in the short run. But an ecosystem's takeovers and dominance of access points lower incentives for entry and innovation, and lower the efficiency of access-point markets with superior alternatives. Hence, the long-run welfare implications of ecosystems are often negative.
Keywords: 330; digital ecosystems; takeover; contestability; entry; envelopment; default effects; steering